Routledge handbook on Sufism - Ridgeon, Lloyd V. J. (Routledge, 2021)
This is a chronological history of the Sufi tradition, divided in to three sections, early, middle and modern periods. The book comprises 35 independent chapters with easily identifiable themes and/or geographical threads, all written by recognised experts in the field. The volume outlines the origins and early developments of Sufism by assessing the formative thinkers and practitioners and investigating specific pietistic themes. The middle period contains an examination of the emergence of the Sufi Orders and illustrates the diversity of the tradition. This middle period also analyses the fate of Sufism during the time of the Gunpowder Empires. Finally, the end period includes representative surveys of Sufism in several countries, both in the West and in traditional "Islamic" regions. This comprehensive and up-to-date collection of studies provides a guide to the Sufi tradition. The Handbook is a valuable resource for students and researchers with an interest in religion, Islamic Studies and Middle Eastern Studies